Reconceiving corporate social responsibility for business and educational outcomes - Mark Anthony Camilleri (Cogent Business & Management, 2016)
There are win win opportunities for big businesses and policy-makers as they nurture human capital with the right knowledge, skills and competences. A thorough literature review suggests that there is a rationale for corporations to collaborate with national governments and other stakeholders in the provision of education and training. In addition, this paper presents qualitative case studies of numerous exemplary firms that have distinguished themselves for their responsible behaviours, particularly towards their human resources and prospective employees. The findings indicate that there is scope for businesses to engage in corporate social responsibility (CSR) initiatives through the provision of educational programmes and continuous professional training and development of workers. Very often, these businesses' underlying objective is to improve their employees' competences, whilst minimising the skill gaps and mismatches in the labour market. In conclusion, this inquiry posits that CSR and stakeholder engagement could boost the employees' morale and job satisfaction, which may in turn lead to lower staff turnover rates and greater productivity levels in workplace environments. It implies that there is potential for the organisational cultures and their business ethos to become more attuned with the governments' educational policies; in order to better respond to the diverse needs of today's learners and tomorrow's human resources.
Keywords: 650